Storytelling : A dental health education media for parents in Rubbik School Community, Semarang, Indonesia - Avina Anin Nasia; Diah Ajeng Purbaningrum; Ira Anggar Kusuma; Tira Hamdillah Skripsa; Yoghi Bagus Prabowo; Valina Khiarin Nisa; Vignarossa Putri Larasati; Wellmanco Pandapotan Manurung (Community Empowerment, 2022)
Parents/caregivers are the most important actors in preventing dental caries since early childhood. Parents have a major role in introducing the importance of maintaining dental health in children. One of the methods that parents can use is by telling stories about dental health to children. Based on previous study showing high prevalence of dental caries among children in Semarang City, we would like to initiate a storytelling training program for parents of students studying at Komunitas Rubbik Indonesia, Semarang. The purpose of this community service program is to provide knowledge of storytelling techniques with children's story books with the theme of dental health. The method that will be used is the creation of dental health education storybooks for children aged 4-7 years and providing training on storytelling techniques for 25 parents of children in the Indonesian Rubbik community. The evaluation of this program shows that parents acknowledge satisfaction with the program and there is a significant difference in the results of pre-test and post-test for parents' knowledge regarding dental health. This activity was able to start the process of using storytelling techniques as a method of dental health education in children.